Ambient noise tomography across Mount St. Helens using a dense seismic array. Issue 6 (3rd June 2017) - Wang, Yadong; Lin, Fan‐Chi; Schmandt, Brandon; Farrell, Jamie
Abstract: We investigated upper crustal structure with data from a dense seismic array deployed around Mount St. Helens for 2 weeks in the summer of 2014. Interstation cross correlations of ambient seismic noise data from the array were obtained, and clear fundamental mode Rayleigh waves were observed between 2.5 and 5 s periods. In addition, higher‐mode signals were observed around 2 s period. Frequency‐time analysis was applied to measure fundamental mode Rayleigh wave phase velocities, which were used to invert for 2‐D phase velocity maps. An azimuth‐dependent traveltime correction was implemented to mitigate potential biases introduced due to an inhomogeneous noise source distribution. Reliable phase velocity maps were only obtained between 3 and 4 s periods due to limitations imposed by the array aperture and higher‐mode contamination. The phase velocity tomography results, which are sensitive to structure shallower than 6 km depth, reveal an ~10–15% low‐velocity anomaly centered beneath the volcanic edifice and peripheral high‐velocity anomalies that likely correspond to cooled igneous intrusions. We suggest that the low‐velocity anomaly reflects the high‐porosity mixture of lava and ash deposits near the surface of the edifice, a highly fractured magmatic conduit and hydrothermal system beneath the volcano, and possibly a small contribution from silicate melt. Key Points: Ambient noise Rayleigh wave tomography was applied across a dense array at Mount St. Helens Biases introduced by inhomogeneous noise source are mitigated by azimuthal traveltime correction Low‐velocity anomaly due to the high‐porosity volcanic edifice and shallowest extent of the magmatic system